Spasm : a novel [large type] - Cook, Robin, 1940- (Thorndike Press large print high octane., 2026)
"When Laurie Montgomery temporarily steps down from her position as Chief Medical Examiner at the OCME to get a break from office politics, she and Jack decide to embark on a weekend getaway. And the timing couldn't be better when they receive a call from Jack's old peer, Robert Neilson MD, about two strange deaths and their potential association with the upswing in Alzheimer's cases in Essex Falls. Deciding this is just what the doctor ordered, Laurie and Jack agree to help, and head upstate. But Essex Falls is far from the rural idyllic town of their imagination. It's apparent that most of the residents are earnest in their undying wish to return America back to the 1950s. Robert tells them the deaths are of two troublemakers, known to be white extremists, in their late twenties. Prior to their deaths, their behavior had been somewhat bizarre with both complaining of muscle spasms, nausea, and off-the-charts anxiety. As Jack and Laurie get to work, they are led to believe that a dangerous bioweapon might be at play, which, in the wrong hands, could threaten the livesof the entire town--and maybe all of America"--